Comparative Study of Dexmedetomidine and Fentanyl as an Adjuvant to Epidural Bupivacaine for Post-operative Pain Relief in Hepato-biliary Pancreatic Surgery (Anwer Khan Modern Medical College Journal, 2019)
Background: Postoperative pain responsible for neurohumoral changes which may cause various organ  dysfunctions, prolong hospitalization and convalescence. Epidural analgesia confers excellent pain relief  and complete dynamic analgesia leading to a substantial reduction in the surgical stress response.Objectives: The aim of the study was to compare the postoperative analgesic effect of dexmedetomidine and  fentanyl as an adjuvant to epidural bupivacaine in adult patients undergoing hepatobiliary pancreatic surgery.Material and method: Eighty(80) patients were selected in the pre anaesthetic checkup room who were going to be  operated for hepatobiliary pancreatic disorders. Each patient in group D(Dexmedetomidine group): Dexmedetomidine  2ml (100 µgm) was mixed with 48ml bupivacaine 0.125% in a syringe 50ml and infused epidurally @ 4ml/hr. for the  postoperative 48 hours. Group F (fentanyl group): Fentanyl 2ml (100 µgm) was mixed with 48 ml bupivacaine  0.125% in a syringe 50 ml and infused epidurally @ 4ml/hr. for the postoperative 48 hours.Results: The quality of analgesia was almost similar with dexmedetomidine and fentanyl group but  perioperative haemodynamic stability was more in dexmedetomidine group than fentanyl group  (p=